Clube de leitura na escola : Estratégias de formação de leitores nos anos finais do ensino fundamental - Vasconcellos, Mariana Fernandes (2025)
The present study focuses on the formation of readers among students in the final years of middle school through the implementation of a reading club in a rural public school in the municipality of Uruguaiana, Rio Grande do Sul, Brazil. The main aim was to implement and analyze a literary reading club project, developed in an extra-class period, in order to monitor the development of reading subjectivity and the reinforcement of the taste for reading. The theoretical framework is based on authors who perceive reading as an aesthetic and transformative experience (Jauss, 1994; Iser, 1996; Rosenblatt, 2002; Larrosa, 2002; Petit, 2008; Bajour, 2020), as well as studies that discuss reading clubs and circles (Álvarez, 2016; Cosson, 2021; Yunes, 2009) and reading diaries (Chambers, 2007; Rouxel, 2000; Souza, 2000). Of an applied nature and qualitative approach, the study used bibliographic research and interventionist action research procedures, involving 12 students in the final years of middle school. The corpus consisted of an initial questionnaire, reading diaries prepared by the participants, and a final questionnaire. The results reveal that the reading club, combined with the use of reading diaries and pedagogical mediation, proved to be a powerful tool for reading formation and developing subjectivity by promoting meaningful reading experiences. It can be concluded that the project contributed to the aesthetic, cognitive, and ethical development of students, reaffirming literary reading as a practice of emancipation, transformation, and humanization.